Ideal jets falling under gravity - Dias, Frederic; Christodoulides, Paul (My University, 1998)
Steady two-dimensional jets of an inviscid and incompressible fluid emerging from a nozzle and falling under gravity are calculated numerically by series truncation. The nozzle is aimed at an angle beta above the horizontal. It is shown that there are flows for all values of beta between 0° and 90° and for all values of the Froude number F. Local solutions are constructed to describe the limiting behavior of the flows as F-->0 and as F-->[infinity]. The problem of a uniform free stream hitting a vertical wall, rising, and forming a jet that falls back upon the oncoming stream is also solved. It is shown that solutions exist only for Froude numbers greater than 2.96.
Keywords: Fluid mechanics